The effects of home country institutions on outward foreign direct investment - Yang Yang (2015)
This dissertation looks into the effects of home country institutions on shaping domestic firms' internationalization, in the form of FDI outflows. In so doing, an Institution Infrastructure (II) theory is developed and tries to provide a more comprehensive explanation for FDI behaviors, a move from home countries to host countries, given that home country effects are paid less attention to in international political economy literature. Therefore, I argue that countries with better institution infrastructures (more investment-friendly policies and better governance) could enhance domestic firms' global competitiveness and reduce their overseas investment risks, and thus will see more FDI outflows. Data built on the FDI outflows of 193 economies in the period of 2003-2013 provide strong support that there is a positive correlation between home country institutions and outward FDI. My findings broaden the understanding of the influence of home country institutions on domestic firms' development, and have substantive implications for policymakers to improve policy effectiveness and government quality. Key words: political economy; the Institution Infrastructure; home country institutions; outward foreign direct investment